Hubungan Konsep Diri dengan Minat Wirausaha pada Mahasiswa Universitas Medan Area - Syafrizaldi Syafrizaldi (Mahesa Research Center, 2018)
In this study the researchers wanted to see how the correlation between self-concept and entrepreneurial interest in Medan Area University Students. After analyzing the statistical data, it appears that the self-concept by asking has a significant correlation. Statistical results show that Rx1y = 0.454, p <0.010, which means that there is a significant correlation between the two variables, with the understanding that the better the self concept, the higher the entrepreneurial interest in students and vice versa. The determinant coefficient (r2) from the correlation between self-concept and entrepreneurial interest is equal to r2 = 0.206. This shows that entrepreneurial interest is formed by self-concept of 20.6%,